Perancangan Layout dan Biaya Material Handling Menggunakan Metode Computerized Relationship Layout Planning (CORELAP) pada fasilitas produksi PT SASL and SONS Indonesia - Owen Rayvaldo Xaverius Moligay; Teguh Oktiarso (Teknik Industri Universitas Ma Chung, 2021)
Efficiency and quality are two crucial factors in the manufacturing industry in Indonesia. PT. SASL and Sons Indonesia is a manufacturing company in the coconut processing industry, with various stages of production separated into different rooms. However, the production room layout was found to be inefficient due to the distance and size between the rooms, which affected the flow of material movement. To address this issue, the Computerized Relationship Layout Method (CORELAP) was used to redesign the layout of each production room and improve the flow of material movement. Factors considered in the redesign included the sequence of production processes, the distance of material movement, and the dimensions of the machine and material handling equipment. The new layout resulted in a material movement distance of 53.963 meters, a reduction of 86.7% from the initial layout's distance of 406.75 meters. This study demonstrates the importance of optimizing production room layout for improved efficiency and material movement, which can ultimately lead to better quality products and customer satisfaction.